Manual para la transformación del Chocho (lupinus mutabilis sweet) en Harina y sus derivados: Pan, Barras Energéticas y Extruidos. - Calvache Tipán, Edwin Adrián (2020)
The Chocho (Lupinus mutabilis Sweet) is a legume that in Ecuador adapts to dry agroecological zones of the Andean region, located between 2,500 and 3,400 meters high, as is the case of Chugchilán, a parish located in the Cantón Sigchos of the province of Cotopaxi where the Project was developed. This legume has a high nutritional content since it has a protein percentage of (47.8%), it is rich in minerals such as: calcium (0.12%), iron (78.45%), fat (18.90%) and fiber (11.07%). The objective of the Integrating Project was to develop a process manual for the transformation of lupine (Lupinus mutabilis Sweet) into flour and its derivatives for the improvement of the economy the different farmers of the communities of the Chugchilán parish (COOPGRANACH). With the help of a virtual library of executed thesis projects (COBUEC), and with the help of a database (Scopus, Scielo, Dialnet), technical scientific information was collected from projects carried out for the development of this work. In the project, the proposed methodology used was announced, indicating what parameters had to be met according to the Ecuadorian Technical Standard NTE INEN 2561 Snacks of vegetable products, NTE INEN 2945 Bread and NTE INEN 2570 Snacks of grains, cereals and seeds.